INFLUENCE OF SEISMOLOGICAL ACTIVITY IN GUBA REGION OF AZERBAIJAN ON MORTALITY FROM CARDIOVASCULAR PATHOLOGIES - Efendiyeva, L.G. (World of Medicine and Biology, 2022)
The purpose of the study was to access the dependence of mortality from cardiovascular diseases on helioseismic indicators in the Guba region of Azerbaijan. To analyze the fatal outcomes of diseases in the Guba region, 653 case histories of patients who died in 2013 from various diseases were studied. The causes of deaths, distribution by sex and age, and a relationship between death accidents and the magnitude of earthquakes, the depth of the epicenter and seismological activity by months were established. The largest percentage of patients died from heart failure 44.9 %, then from acute coronary syndrome (22.1 %), from acute cerebrovascular accident (19.1 %) and from hypertensive crisis (2.9 %). The maximum number of deaths was at a magnitude of 1.1–2.0 ml (34.8 %). Depending on the depth of earthquakes, the maximum number of deaths was at the process depth less than 10 km (34.2 %). Thus, the study of seismological activity makes it possible to assess environmental and emergency situations with a high probability, to provide for preventive measures.